“Dinámica de extraccion de nutrientes en plantones de cacao (theobroma cacao L.) colectados de tres clones y un híbrido bajo condiciones de vivero en el distrito de la banda de shilcayo” - Torres Vásquez, José Luis (2014)
The research was conducted in 2013 at the lnstitute of Tropical Crops (ICT), Experimental Station Juan Bernito district of Shilcayo geographically located at 06 º 30 '07" south latitude and 76 º 20' 09 " west longitude with an altitude of 360 msnmm. The research consisted in evaluating "The Dynamics of nutrient extraction in cacao seedlings (Theobroma cacao L.), collected from three clones and one hybrid under conditions of nursery in Banda Shilcayo District. The treatments were clones of cacao: TO (Hybrid), T1 (ICS-6), T2 (ICS-39) and T3 (SCA-6), assessments were performed at 15, 30, 60, 90 and 120 days. Design was used completely randomized with 4 treatments and 3 comments. The variables were evaluated and statistically analyzed: Analysis of seed and testa, soil analysis, plant tissue analysis, stem height, stem diameter, number of leaves and leaf area. Statistical analysis showed that this K was the element absorbed by the plant at different periods leading treatment T2 (ICS-39) and accumulate it in the root, stem and leaves. Moreover, the Fe was present at high levels in the plant, found in greater proportion in the composition of the root in the first assessments. 165